Ceará PforR : Technical Assessment - World Bank (Washington, DC, 2014)
The Government of Ceará has asked for the Bank s support in implementing its multi-year plan (Plano Plurianual or PPA) for 2012-15. The objectives of the Plan are to promote equitable social development, sustainable economic development and to contribute to the emergence of a more efficient and participatory public sector.The activities to be supported have been chosen on the basis of the importance to these goals, the state s commitment to and the Bank s capacity, in view of its experience in other Brazilian states and elsewhere, to contribute to improving their design and execution. The PforR will build on previous Bank support for public sector reform by strengthening results-based management within sector agencies and providing incentives for collaboration among agencies and with the private sector. This will contribute to strengthening the implementation of Government programs in the following areas: skills development, early childhood development and water quality.